Prognostic Impact of Stimulator of Interferon Genes Expression in Triple Negative Breast Cancer - Tetsuyo Maeda; Makiko Ono; Tomo Osako; Tomohiro Chiba; Satoko Baba; Asumi Iesato; Yukinori Ozaki; Yuka Inoue; Natsue Uehiro; Yoko Takahashi; Takayuki Kobayashi; Takahiro Kogawa; et al. (Cancer Medicine)
ABSTRACT Background Patients with triple negative breast cancer (TNBC) who have a poor response to neoadjuvant chemotherapy (NAC) have worse survival and new treatment strategies need to be developed. TNBC is considered a subtype in which the cyclic GMP‐AMP synthase (cGAS) is linked to the stimulator of interferon genes (STING) pathway, an innate immune response that recognizes cytosolic nucleic acid components, is activated when DNA damage occurs, and is attracting attention as a new therapeutic target. Methods Patients with TNBC who underwent surgery following NAC and for whom pre‐ and post‐treatment tissue specimens were available were enrolled in this study. To examine the association of STING expression with immune profiles and prognosis, STING, cGAS, CD8, and programmed cell death ligand 1 (PD‐L1) expressions in tumor cells (TCs) and immune cells (ICs), and tumor infiltrating lymphocytes (TILs) were assessed using immunohistochemistry of specimens obtained at pre‐treatment and at surgery. Results Ninety‐one cases were eligible, of which 68 cases were evaluable and included in the analysis. The high STING expression at baseline was marginally correlated with TILs, but not with CD8+ cells or PD‐L1 expression. Patients with sustained high expression of STING before and after NAC had a significantly poorer prognosis than that of others for distant recurrence‐free survival and breast cancer‐specific survival independent of nodal status, lymphatic invasion and therapeutic effects (p = 0.024 and 0.014, respectively). Conclusion TNBCs with sustained high STING expression following NAC demonstrated a poor prognosis and will be a target for new treatment strategies.